A kind of sludge dehydration deodorant and preparation method thereof

By using the synergistic effect of quaternized tannin-glutaraldehyde and modified zeolite in sludge treatment, a multi-stage channel network and chemical deodorization system are formed, which solves the problem of low odor control and dehydration efficiency in sludge treatment. It achieves efficient sludge dehydration and deodorization effects.

CN119349841BActive Publication Date: 2025-02-25SICHUAN UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411912675.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-02-25
Estimated Expiration
2044-12-24

AI Technical Summary

Technical Problem

The foul odor control and dehydration efficiency during sludge treatment is low, resulting in poor treatment process effect and economicality, and there are problems such as large equipment investment, high operating costs, low efficiency and impact of hydrated layers.

Method used

Using a sludge dehydration deodorant, including quaternized tannin-glutaraldehyde, cationic polyacrylamide, calcium carbonate and modified zeolite, through the synergistic effect of quaternized tannin-glutaraldehyde and modified zeolite , forming a micropore-macropore multi-stage channel network and a chemical deodorization system to achieve a dual fixation mechanism between physical coating and chemical bonding.

Benefits of technology

It significantly improves the dehydration efficiency and deodorization effect of the sludge, ensures the stable dispersion of modified zeolites, improves the mechanical strength and stability of the flocs, and realizes safe and environmentally friendly sludge treatment and resource utilization.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention belongs to the field of sludge treatment, and discloses a sludge dehydration deodorant and a preparation method thereof. A sludge dehydration deodorant comprises the following raw materials in parts by weight: 5 to 20 parts of quaternized tannin-glutaraldehyde, 1 to 10 parts of cationic polyacrylamide, 20 to 50 parts of calcium carbonate, and 10 to 30 parts of modified zeolite; wherein the modified zeolite is obtained by using hexadecyltrimethylammonium bromide to modify zeolite and then grafting hydroquinone, and has phenolic hydroxyl and silicon hydroxyl groups on the surface; the quaternized tannin-glutaraldehyde is obtained by coupling reaction of quaternized tannin and glutaraldehyde. In the sludge dehydration deodorant raw materials provided by the present invention, quaternized tannin-glutaraldehyde and modified zeolite form a synergistic effect at two levels of spatial structure and chemical action, and the micropore-macropore multi-level channel network formed in space significantly improves the dehydration efficiency; the complementary effect of quaternary ammonium groups and phenolic hydroxyl groups in chemistry realizes a full range of deodorization effects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of sludge treatment, and in particular to a sludge dehydration deodorant and a preparation method thereof. Background Art

[0002] In the field of sludge treatment, odor control and dehydration efficiency have long been two key technical problems that have plagued the development of the industry. They not only directly affect the effectiveness and economy of the treatment process, but are also closely related to environmental protection and public health.

[0003] The odor of sludge mainly comes from the anaerobic decomposition process of organic matter in it. The gases produced, such as hydrogen sulfide, ammonia and methyl mercaptan, not only have a bad smell, but may also cause harm to human health. Traditional odor control methods include chemical deodorization, biological deodorization, physical adsorption and masking methods, but these methods have more or less problems such as unstable effects, high costs, and possible introduction of secondary pollution. On the other hand, sludge dewatering, as a key link in reducing sludge volume and reducing subsequent treatment costs, also faces huge challenges. Common dehydration methods such as mechanical dehydration, natural dehydration and chemical conditioning are often restricted by factors such as large equipment investment, high operating costs, low efficiency, and susceptibility to environmental influences in practical applications. In particular, the hydration layer formed by colloidal substances in sludge and bacterial extracellular polymers (EPS) seriously affects the dehydration effect, and traditional methods are difficult to effectively destroy these structures.

[0004] What is more difficult is that existing technologies often focus on a single problem, either focusing on odor control or focusing on improving dewatering efficiency. This separate treatment method not only increases the overall treatment cost, but also may lead to process complexity and increased operational difficulty. In some cases, the solution to one problem may aggravate another problem. For example, some chemical deodorizers may reduce the dewatering performance of sludge, which further increases the technical difficulty. Summary of the invention

[0005] The purpose of the present invention is to provide a sludge dehydration deodorant and a preparation method thereof, which are used to solve the odor problem and dehydration problem in the sludge treatment process, comply with the principle of sustainable development, and provide a safe and environmentally friendly solution for sludge treatment and resource utilization.

[0006] To achieve the above object, on the one hand, the present invention provides a sludge dehydration deodorant, comprising the following raw materials in parts by weight: 5 to 20 parts of quaternary ammonium tannin-glutaraldehyde, 1 to 10 parts of cationic polyacrylamide, 20 to 50 parts of calcium carbonate, and 10 to 30 parts of modified zeolite;

[0007] The modified zeolite is a zeolite modified by hexadecyltrimethylammonium bromide and then grafted with hydroquinone, and has phenolic hydroxyl groups and silanol groups on the surface;

[0008] The quaternized tannin-glutaraldehyde is obtained by coupling reaction of quaternized tannin and glutaraldehyde.

[0009] Preferably, the tannin in the quaternized tannin-glutaraldehyde is selected from any one of tannin, gallic tannin and catechin.

[0010] Preferably, the preparation method of quaternized tannin-glutaraldehyde is: dissolving quaternized tannin in deionized water, adding glutaraldehyde, and reacting at room temperature at pH 7.5-8.5 for 1.5-2.5 hours.

[0011] Preferably, the molar ratio of glutaraldehyde to quaternized tannin is (0.5-2):1.

[0012] Preferably, the preparation method of the modified zeolite is: reacting hexadecyltrimethylammonium bromide modified zeolite with hydroquinone methanol solution at 65-75°C, pH 7.5-8.5, under nitrogen atmosphere for 3-5 hours, cooling to room temperature and filtering, collecting the solid product, washing, drying, roasting, grinding and sieving.

[0013] Preferably, the mass ratio of hexadecyltrimethylammonium bromide modified zeolite to hydroquinone is 1:(0.1-0.5).

[0014] Preferably, the calcination is carried out at 540-560° C. for 5-7 hours.

[0015] On the other hand, the present invention provides a method for preparing the above sludge dehydration deodorant, comprising: mixing the raw materials, granulating, drying and sieving.

[0016] Preferably, the granulation speed is 30-40 rpm and the time is 15-20 min.

[0017] Preferably, the drying is vacuum drying at 50-60° C. for 4-5 h.

[0018] Compared with the prior art, the present invention has the following beneficial effects:

[0019] 1. In the sludge dehydration deodorant raw materials provided by the present invention, quaternized tannin-glutaraldehyde and modified zeolite form a synergistic effect in terms of spatial structure and chemical action. The microporous-macroporous multi-level channel network formed in space significantly improves the dehydration efficiency; the complementary effect of quaternary ammonium groups and phenolic hydroxyl groups in chemistry achieves a full range of deodorization effects.

[0020] 2. The sludge dehydration deodorant provided by the present invention ensures the stable dispersion of the modified zeolite in the flocs through the dual fixing mechanism of physical coating and chemical bonding, effectively avoiding the problem of easy agglomeration and poor dispersibility of functional components in traditional technologies. At the same time, the multi-point cross-linking effect of the glutaraldehyde group forms a stable three-dimensional network structure, which greatly improves the mechanical strength and stability of the flocs. DETAILED DESCRIPTION

[0021] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0022] The first embodiment of the present invention provides a sludge dehydration deodorant, comprising the following raw materials in parts by weight: 5-20 parts of quaternary ammonium tannin-glutaraldehyde, 1-10 parts of cationic polyacrylamide, 20-50 parts of calcium carbonate, and 10-30 parts of modified zeolite; wherein the modified zeolite is obtained by grafting hydroquinone onto hexadecyltrimethylammonium bromide-modified zeolite, and has phenolic hydroxyl groups and silicon hydroxyl groups on the surface; the quaternary ammonium tannin-glutaraldehyde is obtained by coupling reaction of quaternary ammonium tannin and glutaraldehyde.

[0023] The mechanism of action of the sludge dehydration deodorant provided by the present invention is as follows:

[0024] The core mechanism of action of sludge dewatering deodorant is mainly reflected in the synergistic cooperation of two functional components: quaternized tannin-glutaraldehyde and modified zeolite. Quaternized tannin-glutaraldehyde is a complex organic compound, whose molecules contain three key structural units with specific functions. The quaternary ammonium group can undergo ion exchange with the negatively charged groups on the surface of sludge particles through electrostatic attraction, and selectively adsorb negatively charged odor molecules such as hydrogen sulfide and thiols; the glutaraldehyde group can undergo cross-linking reaction with nitrogen-containing compounds such as proteins and amino acids in the sludge to form a stable covalent bond network structure, and can react with nitrogen-containing odors such as ammonia and amines to generate stable Schiff base compounds; the polyphenol structure in the tannin molecule not only enhances the stability of the flocs through hydrogen bonding, but also can adsorb various polar odor molecules.

[0025] Modified zeolite is another key functional component. After being modified with hexadecyltrimethylammonium bromide and grafted with hydroquinone, a unique composite structure is formed. The three-dimensional pore structure of zeolite itself provides sufficient space for physical adsorption. The introduction of hexadecyl long chains significantly improves the adsorption capacity of malodorous gases, and the grafted hydroquinone not only increases the number of phenolic hydroxyl groups on the surface, but also forms a synergistic effect with the silanol group on the surface of the zeolite to construct a unique bifunctional active site. In the deodorization process, the phenolic hydroxyl group mainly removes alkaline odors such as ammonia through acid-base neutralization, while the silanol group provides additional polar adsorption sites to remove various malodorous gases through the dual effects of physical adsorption and chemical reaction.

[0026] The synergistic effect between quaternized tannin-glutaraldehyde and modified zeolite is mainly manifested in two aspects: spatial structure and chemical action. In terms of spatial structure, the glutaraldehyde group in the quaternized tannin-glutaraldehyde molecule contains two aldehyde groups (-CHO), which can undergo cross-linking reactions with the amino groups (-NH2) of nitrogen-containing compounds such as proteins and amino acids in sludge. Since there are multiple reaction sites on each molecule, a three-dimensional network structure will eventually be formed. When this network structure is formed, the modified zeolite particles with a regular porous skeleton structure will be naturally "embedded" into it. This embedding is achieved through the physical coating of the zeolite particles by the network structure, and is also strengthened by the chemical bonds formed between the zeolite surface active groups and the network structure. This dual fixation mechanism of physical coating and chemical bonding effectively ensures that the zeolite particles can be stably dispersed without agglomeration.

[0027] In terms of pore structure, the system forms a unique double-layer channel: zeolite provides a regular microporous structure, while the network structure of quaternized tannin-glutaraldehyde forms a mesoporous channel. This multi-level pore system combining micropores and macropores can more efficiently extract water from sludge and significantly improve dehydration efficiency. At the same time, at the chemical action level, the quaternary ammonium group and the phenolic hydroxyl group form a complementary deodorization system that can target different types of odor molecules at the same time, thereby comprehensively improving the deodorization effect.

[0028] To further optimize system performance, the sludge dehydration and deodorization agent also contains other important auxiliary components. Cationic polyacrylamide and quaternary ammonium tannin-glutaraldehyde are used together to significantly enhance the flocculation effect.

[0029] Through this multi-component collaborative design, the sludge dewatering deodorant exhibits excellent comprehensive performance in practical applications: it not only has efficient dehydration ability, but also can achieve a long-lasting and stable deodorization effect.

[0030] In some preferred embodiments, the preparation method of quaternized tannin-glutaraldehyde is: dissolving quaternized tannin in deionized water, adding glutaraldehyde, and reacting at room temperature at pH 7.5-8.5 for 1.5-2.5 hours; the molar ratio of glutaraldehyde to quaternized tannin is (0.5-2):1.

[0031] In some preferred embodiments, the preparation method of the modified zeolite is: reacting the hexadecyltrimethylammonium bromide modified zeolite with a methanol solution of hydroquinone at 65-75°C, pH 7.5-8.5, and a nitrogen atmosphere for 3-5 hours, cooling to room temperature and filtering, collecting the solid product, washing, drying, roasting, grinding and sieving; the mass ratio of the hexadecyltrimethylammonium bromide modified zeolite to hydroquinone is 1: (0.1-0.5).

[0032] It should be noted that the preparation methods of quaternary ammonium tannin and cetyltrimethylammonium bromide modified zeolite are both methods disclosed in the prior art. The present invention is based on the quaternary ammonium tannin obtained in the prior art, and a coupling reaction is carried out with glutaraldehyde, and hydroquinone is grafted on the cetyltrimethylammonium bromide modified zeolite to achieve dehydration and deodorization of sludge.

[0033] The tannin in the quaternized tannin-glutaraldehyde may be selected from any one of tannin, gallic tannin and catechin.

[0034] The second aspect of the present invention provides a method for preparing a sludge dehydration deodorant, comprising: mixing various raw materials, granulating, drying and sieving.

[0035] The specific methods of granulation, drying and sieving in the present invention are all commonly used methods in the art, and the final particle size can be determined by those skilled in the art according to the use environment of the sludge dehydration and deodorant.

[0036] Exemplarily, the granulation speed is 30-40 rpm, and the time is 15-20 min; and the drying is vacuum drying at 50-60° C. for 4-5 h.

[0037] In order to make the technical solution of the present invention clearer, the sludge dehydration deodorant and its performance are described in detail through a number of specific embodiments below.

[0038] In the following examples, "parts" are all "parts by weight".

[0039] The sources of some chemicals and reagents used in the examples described below are as follows:

[0040] Pentylene glycol, cationic polyacrylamide, and calcium carbonate were purchased from Shanghai MacLean Biochemical Technology Co., Ltd.

[0041] Example 1

[0042] The sludge dehydration deodorant comprises the following raw materials: 18 parts of quaternized tannin extract-glutaraldehyde, 6 parts of cationic polyacrylamide, 30 parts of calcium carbonate and 22 parts of modified zeolite.

[0043] Among them, the preparation method of quaternized tannin extract-glutaraldehyde is: dissolving quaternized tannin extract in deionized water, adjusting the pH to 8.0, slowly adding glutaraldehyde solution, stirring and reacting at room temperature for 2 hours after the addition is completed, dialyzing with deionized water as a dialysis medium for 48 hours, and freeze-drying to obtain quaternized tannin extract-glutaraldehyde; the molar ratio of glutaraldehyde to quaternized tannin extract is 1:1.

[0044] The preparation method of the modified zeolite is as follows: dissolving hydroquinone in anhydrous methanol to obtain a hydroquinone methanol solution; mixing the hexadecyltrimethylammonium bromide modified zeolite with the hydroquinone methanol solution, adjusting the pH to 8.0, heating to 70°C, controlling the stirring speed at 300rpm, and reacting for 4 hours under nitrogen protection; cooling to room temperature, filtering, collecting the solid product, and washing with anhydrous methanol, and vacuum drying at 60°C for 12 hours; heating to 550°C at a heating rate of 2°C / min, calcining at 550°C for 6 hours, and naturally cooling to room temperature; grinding the calcined sample into fine powder, passing through a 100-mesh sieve, and obtaining the hexadecyltrimethylammonium bromide modified zeolite grafted with hydroquinone; the mass ratio of the hexadecyltrimethylammonium bromide modified zeolite to the hydroquinone used is 1:0.4.

[0045] Preparation method of sludge dehydration deodorant: after mixing various raw materials, granulation is carried out at a rotation speed of 30-40rpm, and the granulation time is 15-20min; the granulated product is vacuum dried at 50-60℃ for 4-5h, passed through a 60-mesh sieve to remove oversized particles, and then passed through a 200-mesh sieve to remove fine powder.

[0046] Example 2

[0047] The sludge dehydration deodorant comprises the following raw materials: 5 parts of quaternized tannin extract-glutaraldehyde, 1 part of cationic polyacrylamide, 20 parts of calcium carbonate and 10 parts of modified zeolite.

[0048] The preparation method of quaternized tannin extract-glutaraldehyde, modified zeolite and sludge dehydration deodorant in this embodiment refers to Example 1. In the preparation process of quaternized tannin extract-glutaraldehyde, the molar ratio of glutaraldehyde to quaternized tannin is 0.5:1, and in the preparation process of modified zeolite, the mass ratio of hexadecyltrimethylammonium bromide modified zeolite to hydroquinone is 1:0.1.

[0049] Example 3

[0050] The sludge dehydration deodorant comprises the following raw materials: 20 parts of quaternized tannin extract-glutaraldehyde, 10 parts of cationic polyacrylamide, 50 parts of calcium carbonate and 30 parts of modified zeolite.

[0051] The preparation method of the quaternized tannin extract-glutaraldehyde, modified zeolite and sludge dehydration deodorant of this embodiment refers to Example 1. In the preparation process of the quaternized tannin extract-glutaraldehyde, the molar ratio of glutaraldehyde to quaternized tannin extract is 2:1, and in the preparation process of the modified zeolite, the mass ratio of hexadecyltrimethylammonium bromide modified zeolite to hydroquinone is 1:0.5.

[0052] Example 4

[0053] The sludge dehydration deodorant comprises the following raw materials: 12.5 parts of quaternized tannin extract-glutaraldehyde, 5.5 parts of cationic polyacrylamide, 35 parts of calcium carbonate and 20 parts of modified zeolite.

[0054] The preparation method of the quaternized tannin extract-glutaraldehyde, modified zeolite and sludge dehydration deodorant of this embodiment refers to Example 1. In the preparation process of the quaternized tannin extract-glutaraldehyde, the molar ratio of glutaraldehyde to quaternized tannin extract is 1.25:1, and in the preparation process of the modified zeolite, the mass ratio of hexadecyltrimethylammonium bromide modified zeolite to hydroquinone is 1:0.3.

[0055] Example 5

[0056] The sludge dehydration deodorant comprises the following raw materials: 18 parts of quaternized gallic tannin-glutaraldehyde, 6 parts of cationic polyacrylamide, 30 parts of calcium carbonate and 22 parts of modified zeolite.

[0057] The preparation method of the quaternized gallic tannin-glutaraldehyde, modified zeolite and sludge dehydration deodorant in this embodiment refers to Example 1. In the preparation process of quaternized gallic tannin-glutaraldehyde, the molar ratio of glutaraldehyde to quaternized gallic tannin is 1:1, and the mass ratio of hexadecyltrimethylammonium bromide modified zeolite to hydroquinone in the preparation process of modified zeolite is 1:0.4.

[0058] Example 6

[0059] The sludge dehydration deodorant comprises the following raw materials: 18 parts of quaternized catechin-glutaraldehyde, 6 parts of cationic polyacrylamide, 30 parts of calcium carbonate and 22 parts of modified zeolite.

[0060] The preparation method of the quaternary ammonium catechin-glutaraldehyde, modified zeolite and sludge dehydration deodorant of this embodiment refers to Example 1. In the preparation process of the quaternary ammonium catechin-glutaraldehyde, the molar ratio of glutaraldehyde to quaternary ammonium catechin is 1:1, and in the preparation process of the modified zeolite, the mass ratio of hexadecyltrimethylammonium bromide modified zeolite to hydroquinone is 1:0.4.

[0061] Comparative Example 1

[0062] Compared with Example 1, the only difference is that quaternary ammonium tannin-glutaraldehyde is not used in the raw materials of the sludge dehydration deodorant, and the other raw materials and preparation method are the same as those in Example 1.

[0063] Comparative Example 2

[0064] Compared with Example 1, the only difference is that modified zeolite is not used in the raw material of the sludge dehydration deodorant, and the other raw materials and preparation method are the same as those in Example 1.

[0065] Comparative Example 3

[0066] Compared with Example 1, the only difference is that quaternary ammonium tannin-glutaraldehyde and modified zeolite are not used in the raw materials of the sludge dehydration deodorant, and the other raw materials and preparation method are the same as those in Example 1.

[0067] Comparative Example 4

[0068] Compared with Example 1, the only difference is that the quaternary ammonium tannin-glutaraldehyde in the sludge dehydration deodorant raw material is replaced by an equal amount of quaternary ammonium tannin, and the other raw materials and preparation method are the same as those in Example 1.

[0069] Comparative Example 5

[0070] Compared with Example 1, the only difference is that the modified zeolite in the sludge dehydration deodorant raw material is replaced by an equal amount of hexadecyltrimethylammonium bromide modified zeolite, and the remaining raw materials and preparation method are the same as those in Example 1.

[0071] Test example

[0072] The sludge dehydration and deodorization agents prepared in the above examples and comparative examples were tested for performance. The sludge to be treated in the test was from a sewage treatment plant, with a water content of 95-98% and a solid content of 2-5%. The specific test method is as follows:

[0073] 1. Dehydration effect test

[0074] (1) Control group test: 1000 mL of sludge to be treated was directly transferred into a plate and frame filter press. The filtration conditions were: pressure 0.6 MPa, time 30 min, and the moisture content of the filter cake was measured;

[0075] (2) Experimental group test: 1000 mL of the sludge to be treated was taken, and 1% of the dehydrating and deodorizing agent of each embodiment and comparative example was added respectively. The stirring conditions were: rapid stirring at 200 r / min for 2 min, slow stirring at 50 r / min for 10 min, and then the sludge was transferred to a plate and frame filter press. The filtration conditions were: pressure 0.6 MPa, time 30 min, and the moisture content of the filter cake was measured.

[0076] (3) Determination of moisture content: Dry the aluminum box at 105°C to constant weight (m1), weigh the sludge sample in the aluminum box (m2), and dry it at 105°C for 24 h to constant weight (m3). The calculation formula is: moisture content (%) = [(m2-m3) / (m2-m1)] × 100%.

[0077] 2. Deodorization effect test

[0078] (1) Sensory evaluation: A five-member evaluation team was organized to grade the odor intensity: 0: no odor; 1: slight odor that can only be detected by careful smell; 2: odor, but not obvious; 3: obvious odor; 4: strong odor. The original sludge and the sludge treated with dehydration and deodorization agents were evaluated separately.

[0079] (2) Gas phase composition analysis: Take equal amounts of sludge and put them into two standard sealed containers of the same specifications. The control group is sludge without dehydration and deodorization agent. The experimental group is added with 1% by mass of sludge treated with dehydration and deodorization agent of each embodiment and comparative example. After sealing, let it stand for 2 h under the same conditions. The concentrations of ammonia and hydrogen sulfide in the two containers are measured by gas chromatography, and the removal rate is calculated: Removal rate (%) = [(C0-C) / C0] × 100%, where C0 is the concentration of the control group and C is the concentration of the experimental group.

[0080] The specific method for determining the concentration of ammonia and hydrogen sulfide is as follows: hydrogen sulfide is analyzed using a gas chromatograph equipped with a flame photometric detector (FPD), the carrier gas is nitrogen, the detector temperature is 90°C, the column box temperature is 50°C, and the carrier gas flow rate is 30mL / min. Ammonia is analyzed using a TCD thermal conductivity detector, the carrier gas is hydrogen, the carrier gas flow rate is 25mL / min, the detector temperature is 250°C, and the column box temperature is 70°C.

[0081] The experimental results are shown in Table 1-2.

[0082] Table 1 Dehydration effect of examples and comparative examples

[0083] .

[0084] Table 2 Deodorization effect of examples and comparative examples

[0085] .

[0086] From the above results, it can be seen that in terms of dehydration effect, the water content of Examples 1-6 decreased by more than 30%, among which Example 1 performed the best, with a decrease of 34.2%. In contrast, the water content of the comparative example decreased by only 12.7-24.2%, which was significantly lower than that of the examples, indicating that the lack of quaternized tannin-glutaraldehyde or modified zeolite would significantly affect the dehydration effect.

[0087] In terms of deodorization effect, Examples 1-6 showed excellent gas removal capabilities, with ammonia and hydrogen sulfide removal rates exceeding 88%. Among them, Example 1 had the most ideal effect, with an ammonia removal rate of 94.8% and a hydrogen sulfide removal rate of 96.7%. The comparative results showed that when quaternized tannin-glutaraldehyde was missing, the removal rate decreased by about 40-50%; when modified zeolite was missing, the removal rate decreased by about 30-40%; if both were missing, the removal rate could only be maintained at a level of 30-40%.

[0088] Comparing the effects of different tannins, the study found that tannin (Example 1) showed excellent comprehensive performance, gallic tannin (Example 5) had a similar effect, and catechin (Example 6) was slightly inferior, but still maintained at a high level. This shows that tannins from different sources can achieve good treatment effects, with the difference in moisture content reduction within 3% and the difference in deodorization effect within 5%.

[0089] From the data performance of Comparative Examples 4 and 5, the degree of modification has a significant impact on the sludge treatment effect. In Comparative Example 4, when only quaternized tannins were used without glutaraldehyde cross-linking, the decrease in sludge moisture content dropped to about 18.5%, and the removal rates of ammonia and hydrogen sulfide dropped to about 55% and 58%, respectively, which shows that the lack of glutaraldehyde cross-linking will significantly weaken the treatment effect. Comparative Example 5 uses zeolite modified only with hexadecyltrimethylammonium bromide, and when hydroquinone is not grafted, the decrease in sludge moisture content is about 20.3%, and the gas removal rate is also reduced to about 60% and 63%, respectively, indicating that the lack of active phenolic hydroxyl groups provided by hydroquinone on the surface of the zeolite will reduce its performance. Compared with the optimal embodiment, the performance of these two sets of data is significantly reduced, which fully confirms the necessity of the two modification steps of glutaraldehyde cross-linking and hydroquinone grafting, which play a key role in improving the dehydration and deodorization effect of the entire system. The experimental results of Comparative Examples 4 and 5 also further verified the importance of a complete modification process to achieve good treatment effects, indicating that simplifying any modification step will lead to a significant decrease in performance.

[0090] Finally, it should be noted that: Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments, or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A sludge dehydration deodorant, characterized in that: The invention comprises the following raw materials in parts by weight: 5-20 parts of quaternary ammonium tannin-glutaraldehyde, 1-10 parts of cationic polyacrylamide, 20-50 parts of calcium carbonate, and 10-30 parts of modified zeolite; The modified zeolite is obtained by grafting hydroquinone onto hexadecyltrimethylammonium bromide-modified zeolite, and has phenolic hydroxyl groups and silanol groups on the surface; The quaternized tannin-glutaraldehyde is obtained by coupling reaction of quaternized tannin and glutaraldehyde.

2. The sludge dehydration and deodorizing agent according to claim 1, characterized in that: The tannin in the quaternized tannin-glutaraldehyde is selected from any one of tannin, gallic tannin and catechin.

3. The sludge dehydration and deodorizing agent according to claim 1, characterized in that: The preparation method of quaternary ammonium tannin-glutaraldehyde is as follows: after dissolving quaternary ammonium tannin in deionized water, glutaraldehyde is added, and the mixture is reacted at room temperature at pH 7.5-8.5 for 1.5-2.5 hours.

4. The sludge dehydration and deodorizing agent according to claim 1 or 3, characterized in that: The molar ratio of glutaraldehyde to quaternized tannin is (0.5-2):

1.

5. The sludge dehydration and deodorizing agent according to claim 1, characterized in that: The preparation method of the modified zeolite comprises: reacting the hexadecyltrimethylammonium bromide modified zeolite with a hydroquinone methanol solution at 65-75° C., pH 7.5-8.5, and a nitrogen atmosphere for 3-5 hours, cooling to room temperature, filtering, collecting solid products, washing, drying, roasting, grinding, and screening.

6. The sludge dehydration and deodorizing agent according to claim 5, characterized in that: The mass ratio of hexadecyltrimethylammonium bromide modified zeolite to hydroquinone is 1:(0.1-0.5).

7. The sludge dehydration and deodorizing agent according to claim 5, characterized in that: The calcination is carried out at 540-560° C. for 5-7 hours.

8. The method for preparing the sludge dehydration deodorant according to any one of claims 1 to 7, characterized in that: Include: After mixing the raw materials, granulate, dry and sieve.

9. The preparation method according to claim 8, characterized in that: The granulation speed is 30-40rpm and the time is 15-20min.

10. The preparation method according to claim 8, characterized in that: The drying is performed under vacuum at 50-60° C. for 4-5 hours.

Citation Information

Patent Citations

  • Method for manufacturing molecular sieve active carbon

    JP2003286022A

  • A tablet for absorbing waste drainage comprising hydrogel

    WO2007116400A2